Continuous and Conformal Lithium Titanate Spinel Thin Films by Solid State Reaction. Issue 8 (23rd May 2018) - Labyedh, Nouha; Put, Brecht; Mel, Abdel-Aziz El; Vereecken, Philippe M.
Abstract : In this work, we report on the fabrication of continuous and uniform thin films by a solid state reaction. The fabrication of spinel Li4 Ti5 O12 thin films was demonstrated by solid state reaction between TiO2 and Li2 CO3 stacked-layers upon thermal annealing. The TiO2 layer was prepared by physical vapor deposition or atomic layer deposition, whereas the Li2 CO3 layer was deposited by chemical solution deposition or atomic layer deposition. The solid state reaction and obtained material properties were investigated on planar substrates. It was found that continuous films with crystalline and stoichiometric Li4 Ti5 O12 can be formed by solid state reaction at temperatures higher than 650°C. The prepared films exhibited Li-ion intercalation characteristics for Li4 Ti5 O12 spinel with the typical flat plateau at 1.55 V (vs Li + /Li) for both charging and discharging. The theoretical capacity of 612 mAh cm −3 was obtained at slow charging rate of 0.1 C with still 45% capacity attainable at 20 C. Interestingly, it was found that the kinetics is strongly dependent on the current collector substrate used. A TiN substrate provided faster Li4 Ti5 O12 electrode kinetics than a Pt substrate, despite a thin anatase interlayer at the TiN/TiO2 / Li4 Ti5 O12 interface, showing the importance of interface or work function matching for high rate lithiation/delithiation performance. In addition, the potential of conformal Li4 Ti5 O12 thin films on high aspect ratio structures was demonstrated.